Association between advanced lung cancer inflammation index and osteoporosis in patients with type 2 diabetes mellitus: evidence from NHANES - Xu, Yifeng; Yan, Zhaoqi; Liu, Liangji (Frontiers in Endocrinology, 2024)
Background: Previous studies have shown a significantly increased prevalence of osteoporosis (OP) in patients with type 2 diabetes mellitus (T2DM), which is closely associated with inflammation and nutrition. This study aimed to investigate the relationship between the advanced lung cancer inflammation index (ALI) and OP in patients with T2DM. Methods: This cross-sectional analysis was conducted based on data from middle-aged and older adults aged 50 years and older with T2DM from the National Health and Nutrition Examination Survey (NHANES).Weighted multivariable logistic regression and linear regression were utilized to investigate the correlation between the ALI and OP with femur bone mineral density (BMD) in individuals with T2DM. Restricted cubic splines (RCS) were employed to assess potential nonlinear relationships, and receiver operating characteristic (ROC) curves were used to evaluate diagnostic accuracy. Results: A total of 1596 patients with T2DM were included in this study, among whom 736 had OP. After adjusting for covariates, the multivariable logistic regression model showed that compared to participants in the fourth quartile of log2transformed ALI, those in the first quartile had an increased prevalence of OP in T2DM (OR = 1.95, 95% CI=1.28-2.96, p < 0.01). The multivariable linear regression model indicated that a low log2-transformed ALI is associated with a low femur BMD.RCS demonstrated a linear dose-response relationship between the ALI index and OP in T2DM (P = 0.686), with the area under the ROC curve being 0.57 (95% CI: 0.54-0.60, p < 0.001), and the optimal cutoff value was 6.04.Our findings indicate that low levels of ALI are independently associated with an increased prevalence of OP in middle-aged and older adults with T2DM in the United States. ALI may serve as a potential biomarker for assessing the prevalence of OP in middle-aged and older adults with T2DM.